2018
DOI: 10.1109/tc.2017.2786249
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Weakly Consistent C Concurrency for Reconfigurable Hardware

Abstract: Abstract-Lock-free algorithms, in which threads synchronise not via coarse-grained mutual exclusion but via fine-grained atomic operations ('atomics'), have been shown empirically to be the fastest class of multi-threaded algorithms in the realm of conventional processors. This article explores how these algorithms can be compiled from C to reconfigurable hardware via high-level synthesis (HLS).We focus on the scheduling problem, in which software instructions are assigned to hardware clock cycles. We first sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Therefore, to ensure that our analysis is valid, we turn to automated tool support. We use the Alloy model checker [5], which has been successfully employed to validate other compiler mappings and optimisations in a weakly consistent setting [28], [3].…”
Section: G Ensuring Correctnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, to ensure that our analysis is valid, we turn to automated tool support. We use the Alloy model checker [5], which has been successfully employed to validate other compiler mappings and optimisations in a weakly consistent setting [28], [3].…”
Section: G Ensuring Correctnessmentioning
confidence: 99%
“…An atomic operation must appear to be instantaneous to all threads and must also obey ordering constraints given by the C memory model [2]. Ramanathan et al [3] showed that atomics can be implemented via HLS by injecting additional scheduling constraints within each thread. Following the standard practice of conventional compilers, memory constraints were determined locally, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Séméria et al [24] and Zhu et al [13] claim to support precise pointer analysis within HLS but they do not evaluate the impact of precision on hardware quality or analysis times, both of which we address. Recent HLS works on synthesising pointer-manipulating programs [25], [26], atomic pointers [27], [28] and dynamic memory allocation [29]- [32] are examples of non-trivial use of pointers, which will increase the need for emphasis on points-to precision in the future.…”
Section: Introductionmentioning
confidence: 99%